1632. Non-Visit-Based and Non-Infection-Related Ambulatory Antibiotic Prescribing. (26th November 2018) - Linder, Jeffrey A; Brown, Tiffany; Lee, Ji Young; Chua, Kao-Ping; Fischer, Michael A
Abstract: Background: Many studies have examined or intervened on ambulatory antibiotic prescribing based on infection-related diagnosis codes. However, clinicians may prescribe antibiotics without seeing patients face-to-face or without documenting an infection-related diagnosis. Methods: We measured the prevalence of non-visit-based and non-infection-related oral, antibacterial–antibiotic prescribing between November 2015 and October 2017 using the EHR of an integrated health delivery system. We examined the visit type (in-person vs. other) and classified prescriptions into 3 mutually exclusive groups based on same-day diagnosis codes: (1) infection-related for prescriptions associated with at least one of 21, 730 ICD-10 codes that may signify infection; (2) non-infection-related for prescriptions only associated with the 72, 519 ICD-10 codes that do not signify infections; and (3) associated with no diagnosis. Results: There were 509, 534 antibiotic prescriptions made to 279, 169 unique patients by 2, 413 clinicians in 514 clinics. Patients had a mean age of 43 years old, were 60% women, and 75% white. Clinicians were 54% women; were 63% attending physicians, 18% residents/fellows, 10% nurse practitioners, and 7% physician assistants; and were 41% medical specialists, 21% primary care clinicians, and 7% surgical specialists. The most common antibiotic classes were penicillins (30%), macrolides (23%), cephalosporins (14%), fluoroquinolones (11%), tetracyclines (10%), and sulfonamides (6%). Clinicians prescribed 20% of antibiotics outside of an in-person visit; prescription encounters were in-person (80%), telephone (10%), order-only (4%), refill (4%), and online portal (1%). Clinicians prescribed 46% of antibiotics without an infection-related diagnosis: 54% of antibiotic prescriptions were infection-related, 29% were non-infection-related, and 17% were associated with no diagnosis. Various look-back and look-forward durations for diagnosis codes changed the results only slightly. Conclusion: Clinicians prescribed 20% of antibiotics outside of in-person visits and 46% of antibiotics without an infection-related diagnosis. Interventions that target visit-based, diagnosis-specific prescriptions miss a large share of antibiotic prescribing. Disclosures: All authors: No reported disclosures.